Short-term effects of six Greek honey varieties on glycemic response: a randomized clinical trial in healthy subjects - Gourdomichali, Theodora; Papakonstantinou, Emilia (European journal of clinical nutrition, 2018)
This randomized, double blind, cross-over study investigated the glycemic response to six Greek honey grades differing in floral source and carbohydrate composition. Eleven clinically and metabolically healthy, fasting individuals (27 ± 7 years; nine women; BMI 24 ± 4 kg/m ) received isoglucidic test meals (50 g available carbohydrate) and 50 g glucose reference, in random order. GI was calculated using the FAO/WHO method. Capillary blood glucose samples were collected at 0, 15, 30, 45, 60, 90, and 120 min. Salivary insulin samples were collected at 0, 60, and 120 min. Subjective appetite ratings (hunger, fullness and desire to eat) were assessed by visual analogue scales (VAS, 100 mm) at baseline and 120 min. Fir and chestnut honeys provided medium GI values (59 and 66, respectively, on glucose scale). Citrus, heather, pine and thyme honeys provided high GI (>70 on glucose scale). Sucrose to oligosaccharides ratio, sucrose content and fructose to glucose ratio were inversely associated with GI (p < 0.05). No differences were observed between honey varieties for fasting glucose, fasting and post-test-meal insulin concentrations and subjective appetite. Honey varieties produced different glycemic responses, although having similar botanical origin and characterization, partly explained by their sucrose to oligosaccharide ratio (by 30%). Fir and chestnut honeys attenuated postprandial glycemic response, which may offer advantages to glycemic control.